A simple and practical criterion for determining a failed His-bundle pacing. (28th December 2020) - Liang, Yanchun; Wang, Na; Yu, Haibo; Xu, Baige; Yan, Xiaolei; Wu, Min; Gao, Yang; Liu, Rong; Xu, Guoqing; Li, Zhenhui; He, Jiaqi; Wang, Zulu; et al.
Abstract: Aims: To establish a simple criterion for determining a failed His-bundle pacing (HBP). This criterion states that if stimulus to QRS end interval is longer than His-bundle potential to QRS end interval ('S-QRSend > H-QRSend') then a failed HBP can be determined. Methods and results: We performed retrospective analysis on 737 pacing tests around His-bundle in 241 patients and prospective analysis on 400 tests in 123 patients. A successful HBP is defined as that whole His-bundle is captured with or without capture of adjacent ventricular myocardium, otherwise, a failed HBP was considered. The output criteria and effective refractory period criteria were used as the gold standards for determining a successful HBP. The gold standards are that if decreasing the pacing output or pacing cycle length to a certain level results in duration or morphology changes of QRS, then a successful HBP is ascertained. In retrospective analysis of patients with normal His-Purkinje conduction, a failed HBP was determined in 31% (154/492) of pacing tests according to 'S-QRSend > H-QRSend'; all of them were validated by the gold standards (specificity = 100%). In prospective study, a failed HBP was confirmed according to the simple criterion with 100% accuracy in 33% (79/241) pacing tests. This simple criterion was also suitable for patients with His-Purkinje conduction disease although cases with 'S-QRSend > H-QRSend' rarely occurred. Conclusion: A failed HBP can be easily and reliably determined solely by 'S-QRSend > H-QRSend' in more than 30% pacing tests.